In Vitro Toxicity Evaluation of New Generic Latanost® and Latacom® as an Ophthalmic Formulation - Ng, Jessica Sze Chia; Tan, Yi Xin; Alwi, Nor Amalina Ahmad; Yee, Kar Ming; Rashid, Ahmad Hazri Abdul; Tan, Ka-Liong; Leong, Chuei Wuei (Jaypee Brothers Medical Publishers (P) LTD, 2024)
Indexed by Scopus